Integration of genomics approach with traditional breeding towards improving abiotic stress adaptation: Drought and aluminum toxicity as case studies - Ishitani, Manabu; Rao, Idupulapati M.; Wenzl, Peter; Beebe, Stephen E.; Tohme, Joseph M. (2004)
Traditional breeding efforts are expected to be greatly enhanced through collaborative approaches incorporating functional, comparative and structural genomics. Potential benefits of combining genomic tools with traditional breeding have been a source of widespread interest and resulted in numerous efforts to achieve the desired synergy among disciplines. The International Center for Tropical Agriculture (CIAT) is applying functional genomics by focusing on characterizing genetic diversity for crop improvement in common bean (Phaseolus vulgaris L.), cassava (Manihot esculenta Crantz), tropical grasses, and upland rice (Oriza sativa L.). This article reviews how CIAT combines genomic approaches, plant breeding, and physiology to understand and exploit underlying genetic mechanisms of abiotic stress adaptation for crop improvement. The overall CIAT strategy combines both bottom-up (gene to phenotype) and top-down (phenotype to gene) approaches by using gene pools as sources for breeding tools. The strategy offers broad benefits by combining not only in-house crop knowledge, but publicly available knowledge from well-studied model plants such as arabidopsis [Arabidopsis thaliana (L.) Heynh.]. Successfully applying functional genomics in trait gene discovery requires diverse genetic resources, crop phenotyping, genomics tools integrated with bioinformatics and proof of gene function in planta (proof of concept). In applying genomic approaches to crop improvement, two major gaps remain. The first gap lies in understanding the desired phenotypic trait of crops in the field and enhancing that knowledge through genomics. The second gap concerns mechanisms for applying genomic information to obtain improved crop phenotypes. A further challenge is to effectively combine different genomic approaches, integrating information to maximize crop improvement efforts. Research at CIAT on drought tolerance in common bean and aluminum resistance in tropical forage grasses (Brachiaria spp.) is used to illustrate the opportunities and constraints in breeding for adaptation to abiotic stresses.